Metastable Pain-Attention Dynamics during Incremental Exhaustive Exercise - Slapšinskaitė, Agnė; Hristovski, Robert; Razon, Selen; Balagué, Natàlia; Tenenbaum, Gershon (Frontiers in Psychology, 2017)
Background: Pain attracts attention on the bodily regions. Attentional allocation toward pain results from the neural communication across the brain-wide network “connectome” which consists of pain-attention related circuits. Connectome is intrinsically dynamic and spontaneously fluctuating on multiple time-scales. The present study delineates the pain-attention dynamics during incremental cycling performed until volitional exhaustion and investigates for the potential presence of nested metastable dynamics. Method: Fifteen young and physically active adults completed a progressive incremental cycling test and reported their discomfort and pain on a body map every 15s. Results: The analyses revealed that the number of body locations with perceived pain and discomfort increased throughout five temporal windows reaching an average of 4.26 ± 0.59 locations per participant. A total of 37 different locations were reported and marked as painful for all participants throughout the cycling task. Significant differences in entropy were observed between all temporal windows except the 4th and 5th windows. Transient dynamics of bodily locations with perceived discomfort and pain were spanned by three Principal Components (PCs). The metastable dynamics of the body pain locations groupings over time were discerned by three time scales: (1) the time scale of shifts (15s); (2) the time scale of metastable configurations (100s), and (3) the observational time scale (1000s). Conclusions: The results of this study indicate that body locations perceived as painful increase throughout the incremental cycling task following a switching metastable and nested dynamics. These findings support the view that human brain is intrinsically organized into active, mutually interacting complex and nested functional networks, and that phenomenological and subjective experiences inherent in pain perception depict identical dynamical principles to the neural tissue in the brain.